2017
DOI: 10.3847/1538-4357/aa56c6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Bulk Lorentz Factors of Outflow Material: Lessons Learned from the Extremely Energetic Outburst GRB 160625B

Abstract: GRB 160625B is an extremely-bright outburst with well-monitored afterglow emission. The geometrycorrected energy is high up to ∼ 5.2 × 10 52 erg or even ∼ 8 × 10 52 erg, rendering it the most energetic GRB prompt emission recorded so far. We analyzed the time-resolved spectra of the prompt emission and found that in some intervals there were likely thermal-radiation components and the high energy emission were characterized by significant cutoff. The bulk Lorentz factors of the outflow material are estimated a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…We note, however, that a spectral analysis of the precursor is reported by Preece et al (2014), who find consistency with synchrotron emission. One of the GRBs included in our sample, GRB 160625B, was already analysed in Ravasio et al (2018), who identified a clear spectral break and a good consistency of the overall spectrum with synchrotron radiation in a marginally fast cooling regime (see also Zhang et al 2018;Wang et al 2017;Lü et al 2017). For homogeneity, here we reanalyse its spectra with the same procedure adopted in this work for the other bursts.…”
Section: The Samplementioning
confidence: 95%
“…We note, however, that a spectral analysis of the precursor is reported by Preece et al (2014), who find consistency with synchrotron emission. One of the GRBs included in our sample, GRB 160625B, was already analysed in Ravasio et al (2018), who identified a clear spectral break and a good consistency of the overall spectrum with synchrotron radiation in a marginally fast cooling regime (see also Zhang et al 2018;Wang et al 2017;Lü et al 2017). For homogeneity, here we reanalyse its spectra with the same procedure adopted in this work for the other bursts.…”
Section: The Samplementioning
confidence: 95%
“…Covino & Gotz 2016). A study of the time variability characteristics is very important because bright GRBs whose spectra have been studied in great detail often found to have spectra deviating significantly from the standard Band function conventionally used to model the GRB spectra (Abdo et al 2009;Izzo et al 2012;Ackermann et al 2010;Vianello et al 2017;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The prompt emission is discussed in detail in Zhang et al (2016), Wang et al (2017), and Lü et al (2017).…”
Section: G-raysmentioning
confidence: 99%